Analysis of Concrete Compressive Strength Using Blood Clam Shells (Anadara Granosa) as a Substitute for Part of Coarse Aggregate - Hidayat, Mohamad Irpan; Prabowo, Yudi Setio (Fakultas Teknik Universitas Tanjungpura, 2026)
The growing demand for concrete has exacerbated the depletion of natural aggregates, necessitating the exploration of alternative materials derived from waste streams. This study examines the feasibility of using blood cockle shells (Anadara granosa), a coastal waste by-product, as a partial replacement for coarse aggregates in structural concrete. Unlike most previous studies that emphasize fine aggregate or filler substitution, this research focuses on coarse aggregate replacement and its influence on both fresh and hardened concrete performance. An experimental program was conducted using 150 mm concrete cube specimens with replacement levels of 0%, 5%, 10%, and 15% by weight, designed in accordance with SNI 03-2834-2000 for a target strength of 25 MPa. All specimens were water-cured and tested at 7, 14, 21, and 28 days. Workability was evaluated through slump tests, while compressive strength was measured using standard compression testing. Results show that workability increased with higher shell content, whereas compressive strength reached an optimum value of 26.5 MPa at 5% replacement before declining at higher substitution levels. These findings demonstrate that low-percentage substitution of blood cockle shell is technically viable and offers a sustainable pathway for structural concrete applications.